The influence of investment-cash flow sensitivity and financially constrained on investment - Wahyuni Rusliyana Sari; Farah Margaretha Leon (University of Merdeka Malang, 2020)
Investment decision making is a crucial process influenced by many factors, such as cash flow. Therefore, it is important for potential investors to understand the stability of cash flow. This study aims to examine cash flow and investment-cash flow sensitivity on investment in manufacturing companies listed in Indonesia Stock Exchange from 2011 to 2015. A panel data methodology by a fixed-effect model with cross-section weights, standard errors, and covariance were utilized. It comprises two models, Panel A and B, with each consisting of all samples, and financially constrained grouping by Kaplan and Zingales-index (KZ-index). The finding that investment-cash flow sensitivity and financially constrained had a significant positive on investment. The result suggests it is important for investment decisions. In panel B, Tobin’s Q was significantly applied to unconstrained companies to prevent a negative impact on sales, with the application of the closing price. The managerial implication of this research is addressed to company managers, potential investors, and readers. In conclusion, cash flow, long-term debt, working capital investment, leverage, and asset turnover impacts on investment for all estimations.JEL Classification: D13, I31, J22 How to Cite:Sari, W. R., Leon, F. M. (2020). The influence of investment-cash flow sensitivity and financially constrained on investment. Jurnal Keuangan dan Perbankan, 24(1), 30-39.DOI: https://doi.org/10.26905/jkdp.v24i1.3475